A qualitative study on factors influencing health workers' uptake of a pilot surgical antibiotic prophylaxis stewardship programme in selected Georgian hospitals. - Sideeka Narayan; Sahil Khan Warsi; Iago Kachkachishvili; Osiko Kontselidze; Mariam Jibuti; Nino Esebua; Ana Papiashvili; Danilo Lo Fo Wong; Ketevan Kandelaki (PLOS Global Public Health)
Antimicrobial misuse in surgical antibiotic prophylaxis (SAP) can include the inappropriate use of broad-spectrum antibiotics or prolonged dosing. In 2021, a pilot antimicrobial stewardship programme (ASP) was launched in Georgia, which involved developing and adapting SAP guidelines, establishing an interprofessional SAP prescribing approach, collecting surgical site infection (SSI) data via routinely collected data and telephonic patient follow-ups, and providing surgical unit staff with prescribing feedback and training on antimicrobial resistance (AMR) and antimicrobial stewardship (AMS). ASP introduction was staggered across ten hospitals over three years. This study explored behavioural determinants of surgical teams' ASP uptake in five hospitals where the ASP was introduced or about to be introduced. Findings primarily concerned epidemiologists' and nurses' ASP-related behaviour. Those at ASP non-introduced hospitals were less involved in the SAP prescribing process, had lower AMR awareness, and lacked professional development opportunities. Those at ASP-introduced hospitals exhibited higher AMR knowledge and felt ASP participation boosted confidence, facilitated work, and furnished key professional development. Results indicate interprofessional collaboration on SAP prescribing supported ASP uptake across teams, and investment in health worker training and administrative encouragement ensured effective ASP participation and implementation. Findings highlight the crucial role of epidemiologists in SAP and illustrate a need for developing Georgian nurses' AMR competencies as a vehicle to address public AMR knowledge gaps. Longer-term ASP uptake will need to consider the regulatory context in which hospitals lack access to national-level SSI data and feedback on SSI reporting but are fined for reporting non-compliance. Despite resource limitations and a small sample size, the study engaged all pilot ASP health workers. Respondents' inexperience of qualitative research participation and ensuant hesitation limited exploration of motivational factors supporting health workers' ASP uptake, which could be explored in further research.